Analisis Keandalan Sistem Jaringan Distribusi 20 kV di PT. PLN (Persero) ULP Panam Menggunakan Metode Reliability Index Assessment (RIA): Analysis of Reliability of 20 kV Distribution Network System in PT. PLN (Persero) ULP Panam With Reliability Index Assessment (RIA) Method - Fanni, Fanni Nurfadillah (Institut Riset dan Publikasi Indonesia, 2022)
The disturbances that often occur in the distribution network of PT. PLN (Persero) ULP Panam greatly affects the reliability value of its distribution network, so it is necessary to evaluate the causes of disturbances and the reliability value of the ULP Panam distribution network using the Reliability Index Assessment (RIA) Method to determine whether the reliability of ULP Panam is still in good condition or not. In this study, using the Reliability Index Assessment (RIA) method and then comparing the calculation results with SPLN 68-2: 1986 and IEEE 1366-2003 with reliability indexes SAIDI, SAIFI and CAIDI. The results of the RIA calculation method obtained SAIDI values ??= 5.25 hours/plg/year, SAIFI = 9.32 times/plg/year, and CAIDI = 0.56 hours/plg/year. Based on SPLN 68-2:1986 SAIDI and CAIDI at PT. PLN ULP Panam can be said to be reliable because its value does not exceed the standard, namely SAIDI of 21 hours/year and CAIDI of 6.56 hours/plg/year. While the SAIFI index at PT. PLN ULP Panam is said to be unreliable because it exceeds the standard limit of SPLN 68-2:1986 which is 3.2 times/year. However, if based on the IEEE 1366-2003 (International) standard, the SAIDI and SAIFI indexes of PT. PLN ULP Panam is said to be unreliable because it exceeds the standard limit, namely SAIDI 2.3 hours/year and SAIFI 1.45 times/year, while the CAIDI reliability index of PT. PLN ULP Panam is said to be reliable because its value does not exceed the IEEE 1366-2003 standard limit of 1.47 hours/year